The Influence of Work Enthusiasm and Work Motivation on The Performance of The South Sumatra Talang Coconut Sector Police Force - Yohanda Rahatama Prakarsa; Siti Komariah Hildayanti; Mohammad Kurniawan DP (ProBisnis : Jurnal Manajemen, 2023)
Work enthusiasm shows the emotional and mental reaction of a person to his work, work enthusiasm affects the quality and quantity of personnel performance. This study aims to analyze the effect of work enthusiasm and work motivation on the performance of Talang Kelapa Sector Police Personnel. The object of this research is the Talang Kelapa sector police personnel as many as 67 people. The analysis technique used in this research is multiple linear analysis which is processed using the help of the Statistical Product and Service Solution (SPSS) computer program version 26. Based on the results of the validity of the questionnaire items, it is obtained that the questionnaire that has been prepared meets the valid criteria or is suitable for use in this study. Based on the results of the multiple linear regression coefficient tests, the final equation Y = 27.245 + 0.339 (X1) + 0.455 (X2) + 2.484 is obtained. Based on the results of the calculation of the coefficient of determination (R2), it is known that the effect of work enthusiasm and work motivation on the performance of Talang Kelapa Sector Police Personnel is 54.3%. Based on the analysis results in the table above, the significance value of the simultaneous F test calculation results of 0.000 is smaller than 0.05. So it can be seen that the work enthusiasm and work motivation variables simultaneously have a significant effect on the performance variable. From the results of the study, it can be concluded that the influence of work enthusiasm and work motivation has a positive and significant effect on the performance of Talang Kelapa Sector Police Personnel.